Structure information from HPLC and on-line measured absorption spectra: flavones, flavonols and phenolic acids - Maria da Graça Campos (Ensino, 2007)
The tools used in scientific research are constantly changing and HPLC with photodiode array detection technique has become an important and popular technology used in studies such as plant extract analysis, drug discovery and development, the monitoring of manufacturing processes and quality assurance. The HPLC/photodiode array technique is also an important base tool of pure science. The authors have provided a compilation of valuable and unique reference material, gathered using strictly controlled conditions, and have developed theoretical rules that will aid users of this technique in the identification of the structures of the titled compound types. These compound types are widely encountered in bioactive plant components. The book will have appeal not only to academic chemists but also for example to biologists, food technologists, pharmacologists, pharmacists, the health supplements industry and the colourant industry. To our knowledge this is the first book of its kind to present and interpret a compilation of actual spectra of a series of authentic compounds, measured under identical and defined conditions that practitioners can use for direct comparison with their own data.